1975
DOI: 10.1111/j.1399-3054.1975.tb03777.x
|View full text |Cite
|
Sign up to set email alerts
|

The ATP Levels Obtained in Photophosphorylation, Glycolysis and Oxidative Phosphorylation in Scenedesmus Titrated with Desaspidin

Abstract: The ATP levels in photophosphoryiation, glycolysisand oxidative phosphorylation, in the unicellalar green alga Scenedesmus obtttsiusculus, were titrated with narrow concentration intei-vals of desaspidin in the presence of different concentrations of 3-(3,4dicliloropheny])-l,l-dimethylurea (DCMU),, which allows the differentiation between nonHjyclic,, pseudocyclic and true cyclic photophosphorylation. The data on photophosphorylative ATP levels were compared with earlier data on total binding of phosphate. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
1977
1977

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…(1963) found that the ATP formation in chloroplasts increased by several-fold by addition of CMU to a ferredoxin-catalyzed cyclic photophosphorylation in an atmosphere of argon. An increase in the ATP level caused by DCMU in Scenedesmus was reported by Kylin and Tillberg (1967b) and studied in more detail by Tillberg and Kylin (1971) and Okkeh and Kylin (1975).…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…(1963) found that the ATP formation in chloroplasts increased by several-fold by addition of CMU to a ferredoxin-catalyzed cyclic photophosphorylation in an atmosphere of argon. An increase in the ATP level caused by DCMU in Scenedesmus was reported by Kylin and Tillberg (1967b) and studied in more detail by Tillberg and Kylin (1971) and Okkeh and Kylin (1975).…”
Section: Introductionmentioning
confidence: 58%
“…The possibility which we call "pseudocyclic" Okkeh 1974, Okkeh andKylin 1975) appears to correspond to the first typeofcyclicphotophosphorylation in the classification of Trebst (1974). One can then envisage that the interactions discussed in the preceding paragraph may lead to the production of electron donors able to act between the two photosystems; so that photophosphorylation ire vivo keeps going even though the water-splitting system has been blocked by 10"^ MDCMU.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations